Nur77 deficiency exacerbates cardiac fibrosis after myocardial infarction through promoting endothelial to mesenchymal transition. (25th November 2020) - Qin, Q; Chen, J.H; Jia, J.B; Qian, J.Y; Ge, J.B
Abstract: Background: Cardiac fibrosis is a reparative process after myocardial infarction (MI), which leads to cardiac remodeling and finally heart failure. Endothelial-to-mesenchymal transition (EndMT) is induced after MI and contributes to cardiac fibrosis after MI. Orphan nuclear receptor Nur77 is a key regulator of inflammation, angiogenesis, proliferation, and apoptosis in vascular endothelial cells. Here, we investigated the role of orphan nuclear receptor Nur77 in EndMT and cardiac fibrosis after MI. Methods and results: Cardiac fibrosis was induced through MI by ligation of the left anterior descending coronary artery. Results suggested that Nur77 knockout aggravated cardiac dysfunction and cardiac fibrosis 30 days after MI. Moreover, Nur77 deficency resulted in enhanced EndMT as shown by increased expression of FSP-1, SM22α, Snail and decreased expression of PECAM-1 and eNOS compared with WT mice after MI. Then we found overexpression Nur77 in HCAECs significantly inhibited IL-1β and TGFβ2 induced EndMT, as shown by reduced transition to a fibroblast-like phenotype and preserved angiogenesis potential. Mechanistically, we demonstrated that Nur77 downregulated EndMT through inhibiting NF-κB-dependent pathway Conclusion: Nur77 plays a role in cardiac fibrosis through inhibition of EndMT, and may be a promising target for therapy of cardiac fibrosis after MI. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Natural Science Foundation of China